Report of the Council at the opening of the twenty-eighth session - Pim, Joseph T. (Statistical and Social Inquiry Society of Ireland, 1874)
The plan, introduced this time twelve-months, of applying to the management of the Barrington Lecture Trust Fund the change which had been previously applied to the public funds given towards scientific instruction in the provinces, has been so far successful. For prelections in Political Economy, given on the old plan of the scientific lectures under the Lecture Committee at Dublin Castle, the Council have, with the assent of Messrs. Edward, Richard, and Arthur Barrington, trustees of the fund, substituted class instruction lectures, given under the auspices of local committees, by lecturers recommended by them, and approved of by the Lecture Committee of the Council.
Read before the Society, 24 November 1874
Keywords: Education; Barrington lectures on political economy; Ninteenth century Ireland; Law reform; 314.15